Lessons learned from the Marmara disaster: Time period under the rubble - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2002)
Objective. To investigate the effect of the time period under the rubble on morbidity and mortality of the crush-syndrome patients after the catastrophic Marmara earthquake that struck northwestern Turkey in August 1999. Design: Observational study. Setting. Consecutive admissions to emergency and intensive care units of 35 reference hospitals that treated the renal victims. Method & Analysis of questionnaires obtained from these hospitals. Patients: A total of 539 of 639 crush-syndrome patients whose time under the rubble was identified in the questionnaires. Results. Mean time under the rubble was 11.7 +/- 14.3 hrs (median, 8 hrs; interquartile range, 6 hrs; range, 0.5-135 hrs). The highest number of patients was entrapped within the 5-8 hrs time stratum, and by the end of 48 hrs, 97% of the victims had been rescued. Nondialyzed victims spent a longer duration under the rubble than dialyzed ones (15.9 +/- 23.1 hrs [median, 7 hrs; interquartile range, 8.5 hrs] vs. 10.3 +/- 9.5 hrs [median, 8 hrs; interquartile range, 6 hrs), p <.001)]. Likewise, in the strata of longer time under the rubble, the percentage of survivors was higher (p =.07). Time under the rubble correlated positively with the number of amputated extremities (p <.001) and admission platelet count (p <.001), and it correlated negatively with admission serum albumin (p <.001). The victims entrapped for >50 hrs (n = 6) were characterized by lower figures of admission blood urea nitrogen (p =.04), serum creatinine (p =.003), hemodialysis sessions, and duration of hemodialysis support (p =.005, for both analyses) compared with victims whose time under the rubble was shorter. Conclusion. Rescue efforts should continue at least for 5 days after the disaster. Time under the rubble is not an adverse prognostic indicator of survival or renal dysfunction for the patients of crush syndrome, probably because only the victims with mild or moderate injuries can survive under the rubble for longer durations.
Keywords: Turkey; acute renal failure; rhabdomyolysis; Marmara earthquake; time period under the rubble; ACUTE-RENAL-FAILURE; 1980 EARTHQUAKE; VICTIMS; RESCUE